Pertanggungjawaban Hukum Platform Marketplace atas Penjualan Barang Palsu dan Dampaknya terhadap Perlindungan Konsumen - Agung Prabowo Widyasaputro; Dewi Iryani; Gradios Nyoman Tio Rae (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The advancement of the digital era has driven the rapid growth of e-commerce in Indonesia; however, it has also led to negative impacts, such as the widespread circulation of counterfeit goods on marketplace platforms. Furthermore, there is a normative inconsistency between the Electronic Information and Transactions (ITE) Law, which applies the Safe Harbor Policy doctrine to limit platform liability and the Consumer Protection Law, which mandates that business actors be held liable for consumer losses. This research aims to: (1) analyze the legal liability of marketplaces regarding the circulation of counterfeit goods and (2) analyze the harmonization of regulations between the Safe Harbor Policy and the obligation for compensation under the Consumer Protection Law. The method employed is descriptive-normative legal research with a statutory approach, utilizing secondary data consisting of primary, secondary and tertiary legal materials. The findings indicate that marketplaces possess a